Type 2 diabetes mellitus and obesity: The synergistic effects on human locomotor function. (December 2022) - Tramonti, Caterina; Iacopi, Elisabetta; Cafalli, Martina; Riitano, Nicola; Piaggesi, Alberto; Chisari, Carmelo
Abstract: Background: Diabetes Mellitus and obesity represent two chronic multifactorial conditions which may induce modifications in human motion strategy. Our study focused on gaining insight into biomechanical aspects of gait occurring in patients affected by both aforementioned pathologies. Methods: One hundred subjects were recruited and divided into four groups: 25 obese-diabetic patients with peripheral neuropathy; 25 obese non-diabetic patients; 25 non-obese diabetic patients with peripheral neuropathy; 25 healthy volunteers participated as a control group. Subjects performed 3-D Gait Analysis while walking barefoot at self-selected speed, performing three consecutive trials. A multivariate analysis of variance test was used to assess spatio-temporal and kinematic data difference in the four groups. Tukey's post-hoc adjustment was applied on multiple groups' comparison. Findings: Diabetic-obese subjects showed increased step width compared to controls, while step and stride length, and walking velocity were reduced. Interestingly, step width presented increased values even compared to diabetic patients. Kinematics data showed a significant reduction in ankle plantarflexion during the push-off phase of the gait cycle compared to controls, and to obese subjects. Furthermore, knee kinematics revealed a reduced peak flexion during the swing time of the gait cycle, compared to controls and diabetic subjects, which resulted in reduced knee dynamic excursion during normal walking compared to healthy subjects. Interpretation: Our data demonstrated that diabetic-obese subjects present gait features typical of both such pathologies. The specific impairment of ankle and knee joint kinematics provides evidence of a synergistic effect of Diabetes Mellitus type 2 and obesity on human ambulatory function. Highlights: Diabetic-obese patients presented worse spatio-temporal parameters of gait. Sagittal plane kinematics showed altered ankle plantarflexion during push-off time. Knee and hip kinematics revealed a reduced peak flexion during the swing time. Diabetic-obese subjects present gait features typical of both these conditions. Results highlight a synergistic effect of such pathologies on human motion strategy.